Chemical composition and antioxidant properties of the essential oil of Nigella sativa L. (Bangladesh Journal of Botany, 2015)
The chemical composition of the essential oil obtained from N. sativa was analyzed by GC/MS and the components identified were: p-cymene (22.05%) followed by ?-thujene (6%), ?-pinene (1.11%), camphene (11%), sabinene (1%), ?-pinene (7%), ?-myrcene (0.21%), ?-phellandrene (0.45%), limonene (0.13), ?-terpinene (5.12%), terpinolene (0.23%), camphor (1%), carvone (0.32%), thymoquinone (20.32%), thymol (10.12%), carvacrol (10%), longicyclene (0.9%) and borneol (0.43). The oils were also subjected to screening for their possible antioxidant activity by using 2,2-diphenyl-1-picrylhydrazyl (DPPH) assays. Thymol (13.0 ± 0.8 ?g/ml), thymoquinone (12.6 ± 0.0 ?g/ml) and carvacrol (12.03 ± 0.0 ?g/ml) showed appreciable antioxidant activity in DPPH test. Antioxidant activity guided fractionation of the oil was carried out by the TLC-bioautography screening and fractionation resulted in the separation of the main antioxidant compound which were identified as thymoquinone (51%), thymol (25%) and carvacrol (8%). DOI: http://dx.doi.org/10.3329/bjb.v44i1.22732 Bangladesh J. Bot. 44(1): 111-116, 2015 (March)